Bioconversion of chicken meat and bone meal by black soldier fly larvae: Effects of straw addition on the quality and microbial profile of larval frass. (1st April 2022) - Wu, Nan; Wang, Xiaobo; Mao, Zhiyue; Liang, Jiaqi; Liu, Xinyuan; Xu, Xiaoyan
Abstract: Meat and bone meal (MBM) is a kind of animal waste with high nutritive values. Bioconversion of MBM by black soldier fly larvae (BSFL) has great potential to obtain high-quality organic fertilizers. However, limited information is available on MBM waste manipulation to enhance BSFL frass quality. In the present study, BSFL were fed with chicken MBM containing increasing levels of rice straw (CK (0%), T1 (1%), T2 (1%), and T3 (3%)). The effects of straw addition into MBM on the quality and microbial profile of BSFL frass were evaluated. Results showed that MBM amended with straw did not significantly affect the body weight of BSFL and most of the nutrients (e.g. pH, EC, TN, TP and Na) in larval frass. Compared to other treatments, T1 sample had the highest organic matter (OM) value, implying proper straw addition could increase OM contents in frass. Fourier transform infrared (FTIR) analysis showed that straw addition might enhance the decomposition of aliphatic carbons and polysaccharides during MBM digestion process. Moreover, T1 sample had the highest microbial richness and Shannon diversity indices. It was supposed that proper straw addition in MBM helped build a more balanced diet and contributed to the BSFL gut health, consequently stimulating the gut microbe-mediated substances transformation or decomposition and promoting the microbial diversity in frass. Compared to CK, straw addition had significant influence on the abundances of Firmicutes, Bacteroidetes and Fusobacteria in frass. Elements including OM, TK and Na played important roles in shaping the microbial profile of BSFL frass. Graphical abstract: Image 1 Highlights: Proper straw addition (1% w / w ) in MBM increased organic matters in BSFL frass. Straw addition enhanced the decomposition of aliphatic carbons and polysaccharides. BSFL frass under T1 treatment had the highest microbial richness and diversity. T1 sample became significantly enriched with Bacteroidetes and Fusobacteria.